2009
DOI: 10.1007/s00403-009-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial regulation of matrixmetalloproteinases and their inhibitors, fibrillar collagens and transforming growth factor-β by Polypodium leucotomos, directly or in dermal fibroblasts, ultraviolet radiated fibroblasts, and melanoma cells

Abstract: The extracellular matrix (ECM) that gives tissue its structural integrity is remodeled in skin aging/photoaging and cancer via the increased expression/activities of matrixmetalloproteinases (MMP), inhibition of the tissue inhibitors of matrix metalloproteinases (TIMP), or inhibition of collagen synthesis. Transforming growth factor-beta (TGF-beta), a predominant regulator of the ECM, is inhibited in aging/photoaging and stimulated in carcinogenesis. P. leucotomos (fern) extract has potential to counteract the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 57 publications
5
112
0
2
Order By: Relevance
“…leucotomos extract inhibits MMP activity directly and the cellular expression of MMPs, while stimulating the expression of TIMPs in dermal fibroblasts and melanoma 2 ISRN Oxidative Medicine cells [2,3]. P. leucotomos extract inhibits the expression of MMPs in epidermal keratinocytes; however, its regulation of elastase activity directly, or cellular expression of TIMPs in epidermal keratinocytes, has not been reported [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…leucotomos extract inhibits MMP activity directly and the cellular expression of MMPs, while stimulating the expression of TIMPs in dermal fibroblasts and melanoma 2 ISRN Oxidative Medicine cells [2,3]. P. leucotomos extract inhibits the expression of MMPs in epidermal keratinocytes; however, its regulation of elastase activity directly, or cellular expression of TIMPs in epidermal keratinocytes, has not been reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of fibrillin has been used as a marker to screen for photoaging repair agents [4][5][6]. P. leucotomos extract stimulates the expression of elastin in dermal fibroblasts and keratinocytes [3]. The regulation of fibrillin by P. leucotomos extract has not been reported and was one of the goals of this research.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] It has been widely reported that natural compounds from plants are potential sources of MMP inhibitors, which may prevent or mitigated UV-induced skin aging. [16][17][18] Stewartia koreana (Theaceae), a deciduous tree, is native to Korea and grows throughout the whole area of Korea.…”
mentioning
confidence: 99%
“…Za główne wykładniki starzenia skóry uznaje się zmniejszenie syntezy kolagenu oraz zwiększenie ekspresji metaloproteinaz macierzy zewnątrzkomórkowej (ang. matrix metalloproteinases -MMP), szczególnie kolagenazy (MMP-1) [8,9]. Dlatego też terapie z zakresu kosmetologii i medycyny estetycznej zmniejszające objawy starzenia skó-ry polegają na przywróceniu niedoborów kolagenu, z jednej strony poprzez pobudzanie jego syntezy, natomiast z drugiej poprzez redukcję MMP rozkła-dających włókna kolagenowe.…”
Section: Odmładzanie Skóryunclassified